Injectable and Antioxidative HT/QGA Hydrogel for Potential Application in Wound Healing - Yikun Ren; Dan Zhang; Yuanmeng He; Rong Chang; Shen Guo; Shanshan Ma; Minghao Yao; Fangxia Guan (Gels, 2021)
Hydrogels have gained a niche in the market as wound dressings due to their high water content and plasticity. However, traditional hydrogel wound dressings are difficult to fully adapt to irregular-shaped wound areas. Additionally, excessive reactive oxygen species (ROS) accumulated in the damaged area impede the wound healing process. Therefore, hydrogels with injectable and antioxidant properties offer promising qualities for wound healing, but their design and development remain challenges. In this study, HT/QGA (tyramine-grafted hyaluronic acid/gallic acid-grafted quaternized chitosan) hydrogels with injectable and antioxidant properties were prepared and characterized. This hydrogel exhibited excellent injectability, favorable antioxidant activity, and good biocompatibility. Moreover, we evaluated the therapeutic effect of HT/QGA hydrogel in a full-thickness skin injury model. These results suggested that HT/QGA hydrogel may offer a great potential application in wound healing.